EFFECT OF NORDIC WALKING ACTIVITIES ON WOMEN BODY COMPOSITION: A CRITICAL REVIEW - Upeniece, Irena; Veseta, Una; Vinberga, Indra; Arnis, Voldemars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Nordic walking (NW) is a particularly health-friendly type of physical activities. Sessions of NW are carried outdoors in “a natural sports hall”. NW with a healthy and biomechanically correct movement evenly employs 600 muscle groups, or 90% of the body muscles. NW is a type of physical activity for developing various biomotor abilities that help in the healthy elimination of overweight. NW activates metabolism and increases energy exchange. Several research have confirmed the positive effects of physical activities for this particular group of patients. Three of the included works of research (Song et al,2013.,Jasinski et al, 2015., Hagner-Derengowska et al, 2015) had a set research quality in the PEDro database, and it corresponded to high quality (6 points out of 10). All included works of research are randomised controlled works of research. The objective of the research is to summarise proof available in sources about the effectiveness of NW in the improvement of health indicators for patients. Research has shown that NW exercise significantly reduces total body fat and is more effective than other forms of physical activity. The results of the study allow to recommend NW as an effective physical activity for improving and maintaining body composition